WRINKLED1 Is Subject to Evolutionary Conserved Negative Autoregulation - Snell, Per; Grimberg, Åsa; Carlsson, Anders S.; Hofvander, Per (Frontiers in Plant Science, 2019)
High accumulation of storage compounds such as oil and starch are economically important traits of most agricultural crops. The genetic network determining storage compounds composition in crops has been the target of many biotechnological endeavors. Especially WRINKLED1 (WRI1), a well-known key transcription factor involved in the allocation of carbon into oil, have attracted much interest. Here we investigate the presence of an autoregulatory system involving WRI1 through transient expression in Nicotiana benthamiana leaves. Different lengths of the Arabidopsis WRI1 promotor region were coupled to a GUS reporter gene and the activity was measured when combined with constitutive expression of different WRI1 homologs from Arabidopsis thaliana, oat (Avena sativa L.), yellow nutsedge (Cyperus esculentus L.) and potato (Solanum tuberosum L.). We could show that increasing levels of each WRI1 homolog reduced the transcriptional activity of the Arabidopsis WRI1 upstream region. Through structural analysis and domain swapping between oat and Arabidopsis WRI1, we were able to determine that the negative autoregulation was clearly dependent on the DNA-binding AP2-domains. A DNA/protein interaction assay showed that AtWRI1 is unable to bind to its corresponding upstream region indicating nondirect interaction in vivo. Taken together, our results demonstrate a negative feedback loop of WRI1 expression and that it’s an indirect interaction most likely caused by downstream targets of WRI1. We also show that it’s possible to release WRI1 expression from this autoregulation by creating semi-synthetic WRI1 homologs increasing the potential use of WRI1 in biotechnological applications.